Implementation of refined Deutsch–Jozsa algorithm in a superconducting qutrit system. Issue 5 (25th November 2016) - Zhao, Jie; Tan, Xinsheng; Lan, Dong; Wu, Haiteng; Xue, Guangming; Yu, Haifeng; Yu, Yang
Abstract: Superconducting quantum circuits are promising candidates for realizing quantum computation due to their intrinsic scalability. Here, we report the implementation of the refined Deutsch–Jozsa algorithm in a 3D superconducting transmon qutrit system. Such 3D superconducting systems usually preserve a relatively long coherence time. A qutrit can take advantage of the third level of a superconducting artificial atom and extends the Hilbert space. Compared with the two‐qubit system used for realizing Deutsch–Jozsa algorithm, the employment of qutrit simplifies the hardware design. This simplification and the intrinsic long coherence time jointly lead to a higher fidelity than in previous transmon implementation [DiCarlo et al., Nature460 (7252), 240–244 (2009)].